2002
DOI: 10.1007/s00125-002-0835-4
|View full text |Cite
|
Sign up to set email alerts
|

Mosapride, a 5HT-4 receptor agonist, improves insulin sensitivity and glycaemic control in patients with Type II diabetes mellitus

Abstract: Aims/hypothesis. We investigated the potential role of mosapride, a 5HT-4 receptor agonist, in glycaemic control in Type II (non-insulin-dependent) diabetic mellitus patients without autonomic neuropathy. Methods. Thirty-four inpatients with Type II diabetes mellitus were randomly assigned to receive either mosapride (5 mg orally three times a day, n=17) or a placebo (n=17) for 1 week (first study). Changes in blood glucose and insulin were determined basally as well as after intravenous glucose loading. Insul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…In the current study, the expression of sweet taste receptors in the duodenum, proximal jejunum, and mid-jejunum-very upper intestine-was increased by the administration of mosapride citrate but not by domperidone, which is also a prokinetic agent. This result corresponds to the observation that only mosapride citrate has the property of enhancing insulin sensitivity and glucose utilization in muscle, unlike domperidone and metoclopramide [4,42], whereas domperidone is effective for diabetic gastropathy as is mosapride citrate [5,43,44]. This enhancement of insulin sensitivity in muscle may be caused by GLP-1 which was increased by the administration of mosapride citrate.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In the current study, the expression of sweet taste receptors in the duodenum, proximal jejunum, and mid-jejunum-very upper intestine-was increased by the administration of mosapride citrate but not by domperidone, which is also a prokinetic agent. This result corresponds to the observation that only mosapride citrate has the property of enhancing insulin sensitivity and glucose utilization in muscle, unlike domperidone and metoclopramide [4,42], whereas domperidone is effective for diabetic gastropathy as is mosapride citrate [5,43,44]. This enhancement of insulin sensitivity in muscle may be caused by GLP-1 which was increased by the administration of mosapride citrate.…”
Section: Discussionsupporting
confidence: 84%
“…This drug has been widely used in Japan, and its significance was again highlighted when it was found to be effective against functional gastrointestinal disorders in a large, randomized clinical trial [3]. The drug has pharmacological properties of reducing hemoglobin A1c (HbA1c) levels in patients with type 2 diabetes [4,5]. Ueno et al [4] demonstrated that mosapride citrate intake increases sugar utilization through enhanced insulin sensitivity in muscle, and Nam et al [6] showed that the drug increased the mobilization of glucose transporters from intracellular pools in muscle; however, the causative mechanisms are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Ueno et al reported that the administration of mosapride citrate for one week significantly improved the glucose responses as evaluated using an intravenous glucose test [12]. They also reported that the administration of mosapride citrate significantly increased the number of and the tyrosine autophosphorylation of insulin receptors as well as the No significant differences in the time profiles and the AUCs for the plasma total GIP levels were observed between the two groups ( Fig.…”
Section: A B a Bmentioning
confidence: 88%
“…Mosapride has no dopamine D 2 receptor antagonist activity, unlike other gastrokinetic agents such as metoclopramide [11]. Mosapride citrate reportedly improves glycemic control in patients with type 2 diabetes [12] and in patients with gastropathy arising from diabetes [13]. By contrast, cisapride, which is another selective agonist of the 5-HT 4 receptor but is presently prohibited because of its effect on the QT interval, has no effect on glycemic control [14, MA, USA) at SRL, Inc. (Tokyo, Japan).…”
mentioning
confidence: 99%
“…In one study, mosapride improved gastric motility in diabetic gastropathy and also improved glycemic control with a corresponding decrease in HgA1C [126,127] .…”
Section: Gastroparesismentioning
confidence: 98%